Osteological alterations in the tucuxi Sotalia fluviatilis (Cetacea, Delphinidae) - Fettuccia, Daniela de C.; Silva, Vera Maria Ferreira da; Simões-Lopes, Paulo César (Iheringia - Serie Zoologia, 2013)
We present a description of osteological alterations observed in the tucuxi, Sotalia fluviatilis (Gervais, 1853) from a sample of 43 specimens. Fractures were the most frequent alterations in the sample (16%), occurring in various regions of the skeleton such as the ribs, hyoid apparatus, transverse and neural processes of vertebrae and scapula. We observed three individuals with ankylosis between the cervical vertebrae and two individuals with morphological changes (cranio-caudally elongated hemal arch and flattened cranial margin of the scapula). The only observed pathology was a case of osteomyelitis in the left dentary, which caused the loss of teeth, deformation of the associated alveoli and the formation of a medial fistula (lingual) for drainage of purulent material. This represents the first record of osteomyelitis in S. fluviatilis.
Alterações osteológicas no tucuxi Sotalia fluviatilis (Cetacea, Delphinidae)
Keywords: Cetacea; Delphinidae; Fistula; Gervais; Sotalia Fluviatilis